One hundred years Swiss Archives of Neurology and Psychiatry—A treasure trove of German-speaking neurology. Issue 1 (11th April 2019) - Kesselring, Jürg
The Swiss Archives of Neurology and Psychiatry was founded in 1917 by Constantin von Monakow (1853–1930), the first professor of neurology at the University of Zurich and founder of the Swiss Neurological Society. The carefully bound booklets of these Archives are to be found completely in the scientific library of the Psychiatric University Hospital Burghölzli in Zürich. It is hoped that this treasure trove of knowledge will be preserved for all those interested in the history of neurology and psychiatry in its integrity. Today's work in and on this archives allows time and again to bring out older works and to present them in the light of more modern concepts. Of medical–historical interest is also the category of obituaries, occurring in almost all issues, virtually a "Who's Who" of neurologists and psychiatrists who have laid the foundations for our subjects.